Silver loaded hydroxyethylacryl chitosan/sodium alginate hydrogel films for controlled drug release wound dressings - Chalitangkoon, Jongjit; Wongkittisin, Marisa; Monvisade, Pathavuth (My University, 2020)
Wound dressings composed of hydroxyethylacryl chitosan (HC) and sodium alginate (SA) were developed with antibacterial activity by loading Ag particles. The formation of Ag particle in the HC/SA films was achieved by an immersion method through in situ chemical reduction of AgNO3 solution and confirmed by FTIR, SEM-EDS, XRD and XRF techniques. The effect of Ag loading in the Ca-crosslinked HC/SA films with different crosslinking density was studied on swelling behavior, mechanical properties, cytotoxicity, antibacterial activity and drug release behavior. The results showed that Ag loading increased swelling degree in phosphate buffer and enhanced mechanical properties. The HC/SA films with Ag loading exhibited antibacterial activity against E. coli and S. aureus as well as no toxicity on Vero cell. In vitro drug release profiles of the films were examined using para-acetylaminophenol, as a soluble model drug. The increase in crosslinking density and Ag loading prolonged drug releasing rate and almost the films showed linearity profiles. It can be concluded that the HC/SA films with Ag loading have a promising potential in modern wound dressings with antibacterial property and controlled drug release.
Keywords: Hydrogel; Hydroxyethylacryl chitosan; Kinetic drug release; Silver particles; Sodium alginate